Investigative teaching sequence: a proposal for teaching School Financial Education - Moraes, Mariana Lafaiete Ferreira; Andrade, Helen Rose de Castro Silva (Educação Matemática Debate, 2025)
In this article we present an Educational Product applied to nineteen students in a 1st year class of New High School, in the Financial Education elective, at a state school in Itamarandiba, MG. In its application, an Investigative Teaching Sequence was developed in six stages: problem, hypothesis, investigation process, interpretation, conclusion and organization of knowledge. During the investigative journey, the students were divided into groups and applied three interview guides to their Parents/Guardians with the themes: family and daily life, social life and personal assets. Finally, the results found highlighted the need for dissemination and consequent appropriation by students through a display of work to the school community, providing opportunities for youth leadership in the school environment.